Risk and Protective Factors for Child Overweight/Obesity Among Low Socio-Economic Populations in Israel: A Cross Sectional Study - Soskolne, Varda; Cohen-Dar, Michal; Obeid, Samira; Cohen, Nitsa; Rudolf, Mary C. J. (Frontiers in Endocrinology, 2018)
Abstract Background and aims: Scientific evidence regarding protective factors that contribute to healthy weight in childhood is limited and is particularly scarce in lower socio-economic populations in different ethnic groups. This study aimed to assess the prevalence of biological, behavioral and psychosocial factors for child overweight/obesity in Jewish and Arab population groups in Israel, and to compare their associations with child overweight/obesity in the two groups. Methods: Children aged 5-6 years were randomly selected from 20 Mother and Child Health clinics in towns and villages of lowest socio-economic ranking in Northern Israel. Children and mothers were invited for a special “One Stop Shop - Preparation for School” visit which included growth measurements. Questionnaires were distributed to mothers for self-report on biological, SES, psychological and lifestyle factors. Perinatal and early nutritional data were retrieved from clinic records. Multivariate analyses using logistic regression models predicting child overweight/obesity were conducted separately for Jewish (N=371) and Arab (N=575) children. Results: Overweight/obesity (BMI≥85th centile) rates were higher in Jewish (25%) than Arab (19%) children. In both Jewish and Arab groups, respectively, maternal BMI (OR=1.10 [95%CI=1.04, 1.17]; OR=1.08 [95%CI=1.04, 1.13]), and child birthweight (OR=1.33 [95%CI=1.04, 1.71]; OR=1.39 [95%CI=1.11, 1.73]) were significant risk factors for overweight/obesity, and maternal self-efficacy regarding child’s lifestyle was significantly protective (OR=0.49 [95%CI=0.28, 0.85]; OR=0.54 [95%CI=0.34, 0.85]). Additionally, four other maternal psychological and child behaviors were significantly associated with overweight/obesity in the Jewish group and two child lifestyle behavior factors in the Arab group. Moreover, significant interactions indicating moderation effects were found only in the Jewish group: maternal education and maternal age moderated the effect of maternal BMI on child overweight/obesity. No other moderation of risk factors was found. Discussion: In this study of children from low SES families, protective factors contributed to healthy child weight alongside risk factors for overweight/obesity. They differed between the population groups, and fewer variables explained overweight/obesity in Arab children. Although further expansion of these findings is required they point at the relevance of protective factors, maternal self-efficacy in particular, for understanding childhood obesity in specific ethnic contexts and for planning culturally adapted prevention programs in disadvantaged populations.